Preliminary Evidence That Resting State Heart Rate Variability Predicts Reactivity to Tactile Stimuli in Rett Syndrome. (January 2020) - Merbler, Alyssa M.; Byiers, Breanne J.; Hoch, John; Dimian, Adele C.; Barney, Chantel C.; Feyma, Timothy J.; Beisang, Arthur A.; Bartolomucci, Alessandro; Symons, Frank J.
Patients with Rett syndrome may manifest altered pain perception/experience and are vulnerable to conditions associated with chronic pain. Pain response is difficult to measure, however, because of severe communicative impairment. There is also documented autonomic dysfunction, including decreased heart rate variability. Given the relation between pain and the autonomic nervous system, we tested the feasibility of using resting heart rate variability to predict nonverbal pain/discomfort behavior during a standardized modified quantitative sensory test in Rett syndrome. All stimulus applications resulted in increased behavioral reactivity compared to baseline, with repeated von Frey significantly greater than all other stimuli. Resting heart rate variability predicted behavioral reactivity to repeated von Frey. These preliminary findings provide feasibility evidence for an integrated autonomic-sensory measurement approach and are consistent at a construct level with preclinical evidence in Rett syndrome. Further work is needed to determine how heart rate variability changes during stimulus application.